Prinsip Netralitas Aparatur Sipil Negara Dalam Pemilihan Kepala Daerah - Sutrisno Sutrisno (Jurnal Hukum IUS QUIA IUSTUM, 2019)
This study aims to determine the factors, weaknesses and components that affect the neutrality of the State Civil Apparatus (ASN) in the recent regional election. This research is a non-doctrinal legal research/socio-legal research/sociology of law study by using the statutory and case approaches in the recent elections in Surakarta City, Sragen Regency and Bantul Regency. The nature of this research is descriptive analysis which intends to provide an overview of the existing condition of the neutrality of ASN in carrying out tasks related to the operation of law in the community. The results of the study concluded that in Surakarta, Sragen, and Bantul, some ASN were not neutral with several contributing factors including personal loyalty, familiar relations, career ambitions, ambiguity of regulations, ineffective law enforcement and low awareness of the community in civilizing the law. The embodiment of the neutrality of ASN in the regional elections can be done by optimally involving the role of several related institutions, including the State Civil Apparatus Commission (KASN), Bureaucratic Leadership, Regional Inspectorate, the Regional Civil Service Agency, the Election Commission and the Election Supervisory Body.